Evidance Based Practice Penerapan Teknik Alternate Nostril Breathing Exercise untuk Membantu Menurunkan Tekanan Darah dengan Masalah Hipertensi - Pandey, Jeclin Veronika; Molintao, Winarsi (JURNAL ILMIAH KESEHATAN MANADO, 2025)
Aging leads to various physical and psychological changes, increasing the risk of degenerative diseases such as hypertension. Known as “The Silent Killer,” hypertension often occurs without symptoms and poses serious health risks in the elderly. Non-pharmacological approaches, such as breathing techniques, are increasingly used to manage blood pressure. This case study involved the application of the Alternate Nostril Breathing exercise as part of nursing care for an elderly patient with hypertension (Mrs. L.H.) at Panti Werdha Damai Ranomuut. The intervention was carried out for 3 consecutive days. The technique involved guided breathing exercises designed to reduce stress and stabilize blood pressure. After three days of intervention, the patient’s blood pressure decreased from 170/100 mmHg to 150/85 mmHg. The patient also reported improved sleep quality and reduced activity intolerance. The Alternate Nostril Breathing technique proved effective as a complementary nursing intervention to help reduce blood pressure in elderly patients with hypertension. This technique can be recommended as part of routine non-pharmacological care for similar cases.